The Effectiveness of Internal Audit in State Owned Company in the Red and White Cabinet Era: The Role of Integrity as a Moderator - Carlos Pangestu, Juan; Simanungkalit, Jobrinson; Whittleliang Hakki, Tandry; Akwila, Karvicha (Journal of Accounting and Finance Management, 2025)
This research is basically to obtain findings on factors that affect the increase in the effectiveness of the performance of the government's Internal Audit department, especially for State-Owned Enterprises (SOEs) so that the findings can be developed again and practiced by other auditors at the Financial Audit Agency (BPK RI) for other government institutions such as Regional Government, OJK, and Departments in Ministries in the Red and White Cabinet to complete problems that occur or the problems underlying this research so that the effectiveness of institutions, especially SOEs, is better and encourages minimizing the potential losses of the state that will be obtained. This study aims to examine the influence of Audit Scope, Senior Management Support and Extrinsic Rewards on Audit Internal Effectiveness moderated by Internal Audit Integrity. In this study, the research population is taken from the government's Internal Audit Department, in this case the Financial Audit Agency which examines SOEs in the cities of Jakarta, Bandung, and Surabaya currently under the Red and White Cabinet government. The type of data used in this study is primary data used as a sample. The research method used in this study is the quantitative research method. Samples were selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of the research expected in this study, are: Audit Scope, Senior Management Support, and Extrinsic Rewards have a significant and positive effect on the Effectiveness of Internal Audit. In addition, Internal Auditor Integrity as a moderation variable can strengthen the influence of Audit Scope, Senior Management Support, and Extrinsic Rewards on Internal Audit Effectiveness.